Is gross morphology of placenta, umbilical cord, and neonatal outcome in well-controlled gestational diabetes mellitus pregnancy different? A case-control study - Parichehr Pooransari; Atefeh Ebrahimi; Nataliya Nazemi; Fariba Yaminifar; Zhila Abediasl (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The relation of placental gross morphology and the outcome of pregnancies complicated with diabetes mellitus in comparison with healthy pregnancies is not known. Identifying significant differences in pregnancy outcomes in Gestational Diabetes Mellitus (GDM) and healthy pregnancies by the means of morphologic measurements can induce the use of antenatal ultrasonography of placental parameters to predict pregnancy outcomes.Objective: This study aimed to evaluate the relationship between placental morphological parameters of the placenta and cord and the outcomes of pregnancies complicated with diabetes mellitus.Materials and Methods: In this case-control study, which was conducted at two referral perinatology center in Tehran between March 2017 and November 2018, 60 pregnant women with GDM who were controlled with either diet or insulin as the case group and 60 pregnant women without GDM as the control group were enrolled. The study population were selected from patients who had their prenatal care and delivery in Mahdieh and Shohadaye Tajrish Hospital. The data was collected by taking sickness history, using data from patients files, and measuring of placental and newborn parameters after delivery. GDM was diagnosed either by 75 gr or 100 gr oral glucose tolerance tests. Placenta parameters, umbilical cord features, and newborn outcomes were compared between the two groups.Results: Placental weight, diameter, number of lobes, thickness, placental weight to-newborn weight ratio, place of umbilical cord insertion, length, coiling, and diameter of the umbilical cord are similar in two groups. Newborn weight, NICU admission, ABG, and Apgar score are also the same in well-controlled GDM pregnancy and pregnancy without GDM.Conclusion: Good controlled GDM causes no difference in placental gross morphology and pregnancy outcome compared to a healthy pregnancy.